2004
DOI: 10.1590/s0100-06832004000400011
|View full text |Cite
|
Sign up to set email alerts
|

Gênese e micromorfologia de solos sob vegetação xeromórfica (caatinga) na região dos Lagos (RJ)

Abstract: Na região dos Lagos do Rio de Janeiro, a existência de um clima mais seco condiciona um ambiente peculiar no sudeste brasileiro, com forte tendência à salinização e xerofitismo. Foram realizados estudos físicos, químicos, mineralógicos e micromorfológicos em transectos de solos da região. Os solos são eutróficos, considerando a ciclagem de nutrientes, o baixo grau de intemperismo e a presença de minerais primários com reserva de nutrientes. Os perfis mais desenvolvidos e latolizados são eutróficos e mostram ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
17

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 15 publications
(14 reference statements)
1
5
0
17
Order By: Relevance
“…The fertility of the studied midden soils was high (Table 2), and greater than in the soils of the surrounding areas (Camargo, 1979;Embrapa, 1979;Moniz et al, 1990;Ibraimo et al, 2004). This agrees with previous, indicating that under prolonged occupation, the soil color is darker and fertility levels higher than of adjacent soils (Kern & Kämpf, 1989;Costa et al, 2002;Lima et al, 2002;Schaefer et al, 2004;Kämpf & Kern, 2005;Corrêa, 2007).…”
Section: Chemical Analysismentioning
confidence: 78%
See 2 more Smart Citations
“…The fertility of the studied midden soils was high (Table 2), and greater than in the soils of the surrounding areas (Camargo, 1979;Embrapa, 1979;Moniz et al, 1990;Ibraimo et al, 2004). This agrees with previous, indicating that under prolonged occupation, the soil color is darker and fertility levels higher than of adjacent soils (Kern & Kämpf, 1989;Costa et al, 2002;Lima et al, 2002;Schaefer et al, 2004;Kämpf & Kern, 2005;Corrêa, 2007).…”
Section: Chemical Analysismentioning
confidence: 78%
“…Al 3+ is absent in the exchange complex, but levels are high in the lithological material of the area, in the form of aluminosilicates (Corrêa, 2007), indicating that at elevated water pH, Al 3+ activity in the medium decreased markedly, aside from the significant organic matter content that acts as a Al 3+ complexant, restricting its activity (Parfitt, 1978). The soils are highly Na + -saturated, indicating strong influence of the salt spray brought by the constant winds to the coastal area, as pointed out by Ibraimo et al (2004) in soils near the sites. Microchemical studies (Corrêa, 2007) showed many K-rich constituents in the sand fraction, e.g., feldspars and micas, and Na-rich components, such as sodic plagioclase, which also helped to increase the Na levels.…”
Section: Chemical Analysismentioning
confidence: 95%
See 1 more Smart Citation
“…Além disso, os solos da caatinga (savana-estépica) também são caracterizados por apresentarem elevada densidade e teor de Na (Oliveira et al, 2009), o que prejudica o crescimento e desenvolvimento das plantas. De fato, elevado teor de Na foi encontrado em savanas-estépicas deste estudo, também semelhante a Luvissolos com caráter solódico no núcleo do domínio da caatinga (Oliveira et al, 2009) e caatinga costeira da região dos Lagos no Rio de Janeiro (Ibraimo et al, 2004).…”
Section: Discussionunclassified
“…Os altos teores de Na + nesses solos podem ser oriundos do material de origem, depositados de áreas vizinhas ou da intensa evaporação em relação à precipitação (Ibraimo et al, 2004).…”
Section: Atributos Químicosunclassified